THE TEACHER OF THE MUHADDITH IN MOVARUNNAHR - Ulug‘murotov Akmal Ziyodullayevich, (EPRA International Journal of Research and Development (IJRD), 2023)
This article talks about the muhaddith who contributed to the development of the early hadith science in Movarunnahir. In fact, Ibn Mubarak achieved a great career in strengthening the Sunnah. It is said that this scholar: "If someone speaks inappropriately about Ibn Mubarak, he will throw a stone at the religion of Islam." He used to write hadiths and separate their sahihs from non-sahihs